1975
DOI: 10.1037/h0076131
|View full text |Cite
|
Sign up to set email alerts
|

Growth of social play with peers during the second year of life.

Abstract: To assess the social interactions between unfamiliar peers, 30 pairs of home-reared children-10 pairs in each of three age groups, 10-12, 16-18, and 22-24 months of age-were observed in an unfamiliar play setting with their mothers. The children contacted their mothers little and interacted more with toys and one another, exchanging smiles, vocalizations, and toys and imitating each other's actions. Contact of the same objects and involvement in the peer's activities with objects increased reliably with age. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
3
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(100 citation statements)
references
References 12 publications
2
93
3
1
Order By: Relevance
“…The use of TV could potentially enhance experimental investigations of social learning between infants and their peers and siblings. Such experiments are complex (Bronson, 1981;Eckerman, Whatley, & Kutz, 1975), in part because the peers do not always adhere to the planned experimental manipulations, and computer-controlled TV peers may be useful in this regard. On the other hand, it is clear that the sounds and sights of TV are very much a part of the infant-toddler natural ecology in modern culture; Steiner (1963) found that about one-third of parents rated "baby sitting" as one of the main advantages of TV, a point also highlighted in the more recent home observations by Lemish and Rice (1986).…”
Section: Discussionmentioning
confidence: 99%
“…The use of TV could potentially enhance experimental investigations of social learning between infants and their peers and siblings. Such experiments are complex (Bronson, 1981;Eckerman, Whatley, & Kutz, 1975), in part because the peers do not always adhere to the planned experimental manipulations, and computer-controlled TV peers may be useful in this regard. On the other hand, it is clear that the sounds and sights of TV are very much a part of the infant-toddler natural ecology in modern culture; Steiner (1963) found that about one-third of parents rated "baby sitting" as one of the main advantages of TV, a point also highlighted in the more recent home observations by Lemish and Rice (1986).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in one of the earliest account of infants' social interactions, Bridges (1933) documented the occurrence of "aggressive attacks" involving biting, hair-pulling and hitting at around 14-15 months of age (see also Brownlee & Bakeman, 1981;Bronson, 1981;Bühler, 1931Bühler, , 1935Dunn & Munn, 1985;Eckerman, Whatley & Kutz, 1975;Goodenough, 1931;Shirley, 1933). More recently, based on mothers' retrospective reports, Tremblay et al (1999) estimated the age of onset of some physically aggressive behaviors among children who manifested the behaviors in question at 17 months of age.…”
Section: Physically Aggressive Behaviors In Children Under Two Years mentioning
confidence: 99%
“…Hypothesis 1 : Girls are never very aggressive The strong claim that girls never develop the ability to be aggressive can be rejected in view of the fact that, when infants first begin to use force against their companions, girls and boys bite, hit and push their peers (Eckerman et al 1975 ;Bakeman & Brownlee, 1982 ;Hay & Ross, 1982 ;Caplan et al 1991;Hay et al 2000, unpublished observations ;Alink et al 2006). In observational studies of infants and toddlers, there are few striking differences in the use of force by girls and boys.…”
Section: Alternative Hypothesesmentioning
confidence: 99%